Internet Use for Lesson Preparation by Pre-service Teachers: A Mixed Methods Study - Uppal, Tajinder (2011)
This exploratory study examined how pre-service teachers use the Internet while preparing lesson plans. Participants (N=30) prepared a literacy-focused lesson using the Internet as their only resource. Data were collected through screen capture technology, tracking where participants went and how they used the Internet, and afterwards, participants’ reflections were obtained through structured interviews. Most participants first visited the Google search engine to find information, or the Ontario curriculum document to check the grade level expectations. Participants conducted three or more Google searches on average, and government, commercial, teacher hosted, and organization sites were the most often visited. These sites were used to find more information on the selected lesson plan, generate ideas by seeing what lessons are available online, look for materials for the lesson, check curriculum expectations and/or, in a few instances, copy a lesson plan directly from a website. Many participants reported regularly preparing lessons in the observed manner.